Effectiveness of Deep Breathing Exercises on Obstructive Sleep Apnea among Type 2 Diabetic Mellitus Patients - Hussein, Ali N.; Hattab, Waffa Abed Ali (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): the study aims to determine the effectiveness of deep breathing exercises on obstructive sleep apnea among type II diabetic mellitus patients. Methods: A quasi-experimental design was carried out on diabetic patients suffering from obstructive sleep apnea through application of intervention program to determine its effectiveness on their sleep apnea. A non-probability (purposive) samples was selected for the purpose of the study, the study started from the first of December 2022 to 30th May 2023. The sample included 40 patients, divided to 2 groups, study group who applied deep breathing exercises for 6 weeks, and control group with no intervention. The questionnaire and the program contents’ validity was determined by a panel of (20) experts to evaluate their clarity, relevance, and appropriateness for the accomplishment of the study. The reliability of the instrument, was done through the use of a test-retest method, where the result was = (0.867) was determined which is acceptable. Data was analyzed using SPSS VERSION 23. Results: There was a significant improvement in the study group after applying deep breathing exercises, where the percentage of improvement of sleep quality and reduce episode of sleep apnea was equal to (85%), while the percentage of risk of obstructive sleep apnea in the control group was equal to (100%). Conclusions: The study confirmed the effectiveness of intervention program for deep breathing exercises on reduce sleep episodes and health-related quality of life. Recommendations: The study recommends the application of current intervention program in the Iraqi hospitals and centers and the need for further studies on more representative sample.